Ultrasound device as a minimally invasive approach for caries dentin removal - Besegato, João Felipe [UNESP]; Melo, Priscila Borges Gobbo de [UNESP]; Bernardi, Adilson César de Abreu; Bagnato, Vanderlei Salvador; Rastelli, Alessandra Nara de Souza [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of this study was to evaluate the efficacy of an ultrasound device and the dentin surface morphology after removal of the caries dentin lesions by removal rate and scanning electron microscopy (SEM). The Knoop hardness test on the bovine dentin blocks (n = 20, 4x4x2mm) was performed to standardize the samples and only those with 38 ± 2 KHN were included. The dentin blocks were submitted to induction of artificial caries lesions, using the bacterial model. Strains of Streptococcus mutans and Lactobacillus acidophilus were used for 7 days. The caries dentin lesion was removed for 1 min, according to two methods: G1 - carbide bur under low-speed rotation (control group) and G2 - ultrasound device under refrigeration. For the removal rate, the samples were weighed 3 times: T0 (before induction), T1 (after induction) and T2 (after removal). Morphology evaluation of the residual dentin surface was performed by SEM. Data normality was verified by Shapiro-Wilk test (p ≥ 0.240). T-test for independent samples was applied to evaluate the removal rate. A significance level of 5% was adopted. G2 provided lower removal rate than G1 (G1: 3.68 mg and G2 = 2.26 mg). SEM images showed different morphological characteristics between the groups. G2 showed absent of smear layer, while G1 showed a visible smear layer over the surface. We concluded that ultrasound device provides minimally invasive removal with residual dentin exhibiting open dentin tubules and no smear layer formation and no bacteria, which infer the removal of the infected tissue.